The robot fact checker prospects and challenges of artificial intelligence use for fact-checking in online Philippine newsrooms - Caling, Rhenzel Raymond; Palalimpa, Renz Joshua A.; Chua, Yvonne T. (Quezon City College of Mass Communication, University of the Philippines, 2023)
Fact checkers across the globe face the increasing presence of artificial intelligence in their work through its involvement in the three steps of fact-checking: claim detection, evidence retrieval and claim verification. But while Al integration is such studied in the West, little is known in the Philippines—the "patient zero" of disinformation. Guided by the actor-network theory, this study examined the local landscape of Al use in fact-checking and the determinants of its adoption. Interviews with 7 Filipino journalists across eight fact-checking newsrooms revealed that all newsrooms use free third-party tools. These programs are employed in all newsrooms' evidence retrieval stages and in most newsrooms' claim detection tasks. Six newsrooms who use AI for two fact-checking steps rank second place in a three-tier system introduced in the study. Key determinants to AI adoption are issues on technology, media competition, audience relation and political context. Reasons related to these determinants are primary hindrances for 16 respondents and motivations for 13 respondents, demonstrating a general hesitance to incorporate more Al into fact-checking. While all respondent, agree that Al must not not check without humans, they long for AI nuanced to national and regional contexts through open-data access and financial support
Vita.
Thesis
Includes bibliographical information (pages 103-133) and appendices (pages 134-161).
Keywords: Artificial intelligence; Fake news -- Philippines; Disinformation -- Philippines; Misinformation -- Philippines